Sobre o uso de conhecimento especialista para auxiliar no aprendizado de Word Embeddings - Santos, Flávio Arthur Oliveira (2018)
Word representations are important for many Natural Language Processing (NLP) tasks. Obtaining good representations is essential since most machine learning methods responsible for solving NLP tasks consist of mathematical models that use these numerical representations, which are capable of incorporating syntactic and semantic information from the words. The so-called Word Embeddings, vectors of real numbers generated by machine learning models, are a recent and popular example of the aforementioned representations. GloVe and Word2Vec are widespread models in literature that learn said representations. However, both attribute a single vectorial representation for each word, so that: (i) their morphological information is ignored and (ii) paraphrases at word level are represented by different vectors. Not using morphological knowledge is considered an issue because that knowledge is composed by very important information, such as: radical, gender and number ending, vowel themed, affixes. Words sharing such features must have similar representations. Paraphrase representations at word level must be similar because they consist of words written differently that share the same meaning. The FastText model tries to solve problem (i) by representing a word as a bag of character n-grams; thus, each n-gram is represented as a vector of real numbers and a word is represented by the sum of its respective n-gram vectors. Nevertheless, using every possible character n-gram is a brute force solution, without any scientific basis, that compromises (or makes unviable) model training performance in most computing platforms available for research institutions since it is computationally costly. Besides, some n-grams do not show any semantic relation with their reference words. In order to tackle this issue, this work proposes the Morphological Skip-Gram model. The formulated research hypothesis states that exchanging the character bag of n-grams for the word bag of morpheme results in words with similar morphems and contexts having similar representations. This model was evaluated in terms of 12 different tasks. These tasks aim to evaluate how well the learned word embeddings incorporate syntactic and semantic information from the words. The obtained results show that the Morphological Skip-Gram model is competitive when compared to FastText, being 40% faster. In order to try solving problem (ii), this work proposes the GloVe Paraphrase method, where information from a paraphrase at word level dataset is used to reinforce the original GloVe method and, as a result, paraphrase vectors end up more similar. The experimental results show that GloVe Paraphrase requires less training epochs to obtain good vectorial representations.